2008
DOI: 10.1177/0145482x0810201105
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of Electronic Mobility Aids for Persons with Visual Impairments: A Literature Review

Abstract: This literature review of existing electronic mobility aids for persons who are visually impaired and recent developments in this field identified and classified 146 products, systems, and devices. The 21 that are currently available that can be used without environmental adaptation are described in functional terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(81 citation statements)
references
References 12 publications
(14 reference statements)
0
80
0
1
Order By: Relevance
“…Electronic Orientation Aids (EOAs) are a second category of devices that provide the VI with some degree of situational awareness and guidance in unknown environments, dealing with more distant environments, aiding in a task sometimes called macronavigation. A review in 2009 of existing electronic mobility aids for the VI identified 146 devices, providing details on 21 commercially available systems that can be used without environmental adaptations [4]. The authors noted that many of the reviewed products are no longer available or are prototypes that are in development or failed to reach the market.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic Orientation Aids (EOAs) are a second category of devices that provide the VI with some degree of situational awareness and guidance in unknown environments, dealing with more distant environments, aiding in a task sometimes called macronavigation. A review in 2009 of existing electronic mobility aids for the VI identified 146 devices, providing details on 21 commercially available systems that can be used without environmental adaptations [4]. The authors noted that many of the reviewed products are no longer available or are prototypes that are in development or failed to reach the market.…”
Section: Introductionmentioning
confidence: 99%
“…The training was implemented in two stages: (1) training all participants (introduction to the use of system technologies used), and (2) individual training (working with the service under real conditions). Before conducting the tests, participants were introduced to: (1) the main goals of the service and the functionality that the service offers, (2) RFID and NFC technologies and types of tags used, (3) how to read tags with the NFC sensor integrated into the mobile phone, (4) how the user interface works and how to use it, (5) what a user ID card is and how to launch the service with it, (6) how to tag objects from the real world (with special attention given to the way in which metal objects and those that contain metal foil are tagged), (7) how to create a voicebased description of objects, (8) how to scan objects, (9) how to delete and re-record audio recording(s), and (10) how to sync audio recordings and how to share audio recordings with other users. It is desirable, especially in the early days of using the service, for users to be able to get help.…”
Section: Trainingmentioning
confidence: 99%
“…The lowest score (3) was given by the older participants (1, 4, and 6). The lowest score (3) for criterion 3 (required attention) was given by the oldest participant (6). Proposed service was evaluated 32% higher for criterion 4 (functionality).…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations